Newborns, infants and epilepsy - the missing piece of software - Janne Lahtiranta; Jaana Lähdetie (Finland, 2022)
Diagnosing epilepsy on a small child is a challenge. A child’s brain undergoes tremendous changes during the first years, creating new neural connections every second. It follows from this that what the parents and the physician may regard as abnormal behavior, can be perfectly normal. However, in some cases the abnormal behavior may be caused by epilepsy. In that case, either a detailed description of the seizure or, preferably, an eye-witness’ recording of it is invaluable in terms of making an accurate diagnosis. Naturally, an EEG is also needed. Obtaining relevant, detailed information from parents is not always a straightforward matter. In order to enable collecting more accurate information about episodes that are potentially epileptic, new practices and technologies are needed. In the following viewpoint we present what can be called the missing piece of software.